Analisis Pendapatan Petani Karet Sub UPP (Unit Pelaksanaan Proyek) Rantau di Kecamatan Hatungun Kabupaten Tapin - Meilani Wulansari; Artahnan Aid; Kamiliah Wilda (Universitas Lambung Mangkurat, 2012)
The study is purposed to know the condition, cost, income and profit of small scale rubber plantation - member of Sub-unit UPP Hatungan in Kecamatan Hatungan, Kabupaten Tapin. Sub-unit UPP Hatungan is a rubber planting project conducted by Forestry and Plantation Agency of Kabupaten Tapin. It was started in 1992-1993 and the rubber plants was planted in 1994-1995. The government financed the plantation until year 5. Then, after start to yield, it was handed over to the farmers. As a return, farmers were obligated to repay the 5 years cost by installment. Total cost on plant age 16 year, calculated by discounted methods, is Rp. 8.383.549,99. while the revenue, income and profit is Rp. 18.400.000; Rp. 15.378.230,98,and Rp. 12.081.115,94, respectively.